A Study on Motivations for Career Switching to Entrepreneurship in Handicrafts Among Women - Deya Gayatri, G; S. Udhayakumar, C (International Journal of Engineering and Technology, 2018)
The handicraft sector in India, due to its rich history and promising growth has been attracting a large number of entrepreneurs in recent times. A significant portion of these are women who have quit their previous careers due to the allure of the handicrafts sector. This study makes a modest attempt to explore the reasons why women choose to switch their careers at various organizations in favor of becoming a handicraft entrepreneur. The methodology employed uses a structured questionnaire which was circulated among women entrepreneurs through mail survey. The data was collected from select 53 women entrepreneurs in India who managed small to medium sized enterprises and who met the criteria of having quit their previous jobs to pursue their current chosen career and it was analyzed through the statistical software S.P.S.S. The results reveal that most of the respondents were motivated to engage in an entrepreneurial career in handicrafts because it made sense, they regarded it as a personal achievement and for some of them it was because they wanted to challenge themselves.Â